2012
DOI: 10.1038/jes.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

Population variability of phthalate metabolites and bisphenol A concentrations in spot urine samples versus 24- or 48-h collections

Abstract: Human exposure to phthalates and bisphenol A (BPA) can be assessed through urinary biomonitoring, but methods to infer daily intakes assume that spot sample concentrations are comparable to daily average concentrations. We evaluate this assumption using human biomonitoring data from Germany and the United States (US). The German data comprised three regional studies with spot samples and one with full-day samples analyzed for phthalate metabolites. The US data included: a study on DEHP metabolites and BPA invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…While NHANES provides data almost exclusively for spot samples, Christensen et al (2012) found that spot urinary concentrations of BPA were fairly comparable to corresponding 24-h average concentrations obtained from a similar population indicating that "spot samples can be used to characterize population distributions of intakes," with caution needed for data at the tail of the distribution. The approach of using spot urinary BPA data to estimate daily intakes of BPA in the US has been described previously Naiman, 2008, 2011;LaKind et al, 2012).…”
Section: Estimating Population Bpa Daily Intakementioning
confidence: 68%
“…While NHANES provides data almost exclusively for spot samples, Christensen et al (2012) found that spot urinary concentrations of BPA were fairly comparable to corresponding 24-h average concentrations obtained from a similar population indicating that "spot samples can be used to characterize population distributions of intakes," with caution needed for data at the tail of the distribution. The approach of using spot urinary BPA data to estimate daily intakes of BPA in the US has been described previously Naiman, 2008, 2011;LaKind et al, 2012).…”
Section: Estimating Population Bpa Daily Intakementioning
confidence: 68%
“…The possibility of misclassification does not appear to be a critical weakness. Although spot urine samples have comparability with corresponding 24-h urine samples for concentration testing, 38 considering the variability of phthalate exposure and the short biological half-life of phthalates, 39 a single urine analysis may be insufficient to measure the exposure over a relatively long time. 40 It is difficult to determine the relationship between the DEHP level and AD at extremely low exposures such as those below the detection limit, and more sensitive methods to detect low-dose exposure are needed.…”
Section: Discussionmentioning
confidence: 99%
“…First, we relied upon a single spot urine sample for assessing BPA exposure. Though no evidence is available regarding long-term average exposures, recent evidence suggests spot samples yield a suitable estimate of average daily [36] and weekly [37] exposures. In a sample of eight CDC employees (4 male, 4 female) examined for one week, it was found that first morning and 24-hour voids had high between-day variance in BPA concentration, while spot urine samples had high within-day but relatively low between-day variance [36].…”
Section: Discussionmentioning
confidence: 99%
“…Though no evidence is available regarding long-term average exposures, recent evidence suggests spot samples yield a suitable estimate of average daily [36] and weekly [37] exposures. In a sample of eight CDC employees (4 male, 4 female) examined for one week, it was found that first morning and 24-hour voids had high between-day variance in BPA concentration, while spot urine samples had high within-day but relatively low between-day variance [36]. Moreover, in a larger study comprising 217 urine samples from 87 male and female patients at an infertility center, Mahalingaiah and colleagues found that a single urine sample correctly classified participants into the highest BPA exposure tertile with sensitivity and specificity equal to 64 and 76 percent, respectively [38].…”
Section: Discussionmentioning
confidence: 99%